2012
DOI: 10.1155/2012/768982
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Airway Smooth Muscle’s Role in Airway Hyperresponsiveness

Abstract: A link between airway smooth muscle (ASM) and airway hyperresponsiveness (AHR) in asthma was first postulated in the midnineteenth century, and the suspected link has garnered ever increasing interest over the years. AHR is characterized by excessive narrowing of airways in response to nonspecific stimuli, and it is the ASM that drives this narrowing. The stimuli that can be used to demonstrate AHR vary widely, as do the potential mechanisms by which phenotypic changes in ASM or nonmuscle factors can contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…It has long been hypothesized that during the development of asthma the ASM undergoes fundamental changes that make it hypercontractile. Bronchoprovocation studies using a wide variety of stimuli have shown that AHR is not specific to one agonist, indicating that the phenomenon is related to a general abnormal behaviour of ASM and not to upregulation of specific agonist receptors ( Curry, 1946 ; Dubois and Dautrebande, 1958 ; Nadel et al, 1965 ; Mcneill and Ingram, 1966 ; Mathé et al, 1973 ; Peters-Golden and Henderson, 2007 ; Driessen et al, 2012 ; Pascoe et al, 2012 ; Hyrkäs-Palmu et al, 2018 ). Another observation that points towards abnormalities in ASM is that a deep inhalation does not cause bronchodilation in asthmatic subjects, and in severe disease may lead to bronchoconstriction ( Fish et al, 1981 ).…”
Section: Airway Hyperresponsiveness In Asthmamentioning
confidence: 99%
“…It has long been hypothesized that during the development of asthma the ASM undergoes fundamental changes that make it hypercontractile. Bronchoprovocation studies using a wide variety of stimuli have shown that AHR is not specific to one agonist, indicating that the phenomenon is related to a general abnormal behaviour of ASM and not to upregulation of specific agonist receptors ( Curry, 1946 ; Dubois and Dautrebande, 1958 ; Nadel et al, 1965 ; Mcneill and Ingram, 1966 ; Mathé et al, 1973 ; Peters-Golden and Henderson, 2007 ; Driessen et al, 2012 ; Pascoe et al, 2012 ; Hyrkäs-Palmu et al, 2018 ). Another observation that points towards abnormalities in ASM is that a deep inhalation does not cause bronchodilation in asthmatic subjects, and in severe disease may lead to bronchoconstriction ( Fish et al, 1981 ).…”
Section: Airway Hyperresponsiveness In Asthmamentioning
confidence: 99%
“…Muscular contraction of the ASM contributes in part to asthmatic bronchoconstriction, but it is presently not known whether AHR in asthmatic individuals arises from fundamental chronic alterations to ASM cells as a result of inflammation, as an adaptive response to changes in the mechanical microenvironment (higher airway resistance), or both (6). The role of ASM hyperplasia, hypertrophy, and the mechanical properties of the ASM including its shortening and relaxation characteristics in AHR have been investigated; however, no clear relationship between ASM characteristics and AHR has so far emerged (35,47).…”
Section: Airway Smooth Musclementioning
confidence: 99%
“…This condition involves the release of eicosanoids derived from the n-6 fatty acid arachidonic acid (ARA), and their actions affect the functional response of bronchial smooth muscles [ 1 , 2 ]. In the pulmonary microenvironment, these bioactive molecules lead to the main feature of asthma: bronchial hyper-reactivity [ 3 , 4 , 5 , 6 ]. Among the various eicosanoids, the presence of 4-series leukotrienes (LTs) has a remarkable effect: they are considered the central mediators of airway hyper-responsiveness and asthmatic bronchoconstriction [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%